International Trade Policy and Class Dynamics in South Africa The Economic Partnership Agreement - Claar, Simone (International Political Economy Series,, 2018)
This book provides an innovative perspective on class dynamics in South Africa, focussing specifically on how economic and trade policy have shaped the interests of two strands of the South African population. As an emerging market, South African political and economic actions are subject to the attention of international trade policy. Claar provides an in-depth class analysis of the contradictory negotiation processes that occurred between South Africa and the European Union on Economic-Partnership Agreements (EPA), examining the divergent roles played by the political and economic elite, and the working class. The author considers their relationships with the new global trade agenda, as well as their differing standpoints on the EPA.